HPV and cervical cancer: screening or vaccination? - Bosch, F X (Nature Publishing Group, 2008)
Following the demonstration of the superior validity of human papillomavirus (HPV) tests in screening for cervical cancer and the arrival of highly efficacious HPV 16 and 18 vaccines, cervical cancer prevention enters a time of sustainable introduction in developing countries. Multidisciplinary efforts and novel protocols are being developed, and challenging situations are being faced to make cervical cancer, still the number two cancer in women worldwide, an eradicable condition.